2019
DOI: 10.1136/bjophthalmol-2018-313723
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of changes in corneal endothelial cell density and central corneal thickness between conventional and femtosecond laser-assisted cataract surgery: a randomised, controlled clinical trial

Abstract: Background/AimTo identify changes in endothelial cell density (ECD) and central corneal thickness (CCT) in eyes undergoing femtosecond laser-assisted cataract surgery (FLACS) compared with conventional phacoemulsification surgery (CPS).MethodsThis is an intraindividual randomised, controlled clinical trial. One eye was randomised to receive FLACS, while the contralateral eye of the same patient received CPS. The femtosecond laser pretreatment included creating main and side-port corneal incisions, capsulotomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…76 While another study found that while there was no difference in ECL between eyes undergoing FLACs or CPS at 6 months, FLACS eyes with FL CCIs had greater ECL than those with manual corneal incisions, suggesting that FL CCIs may negate some of the benefit of reduced phacoemulsification time on ECL. 77 More recently, in two randomised prospective studies by Dzhaber et al 78 in 134 eyes and Roberts et al 49 in 400 eyes showed no post-operative differences between FLACS and CPS at 3 and 1 month, respectively.…”
Section: Fl-assisted Nuclear Fragmentationmentioning
confidence: 94%
See 1 more Smart Citation
“…76 While another study found that while there was no difference in ECL between eyes undergoing FLACs or CPS at 6 months, FLACS eyes with FL CCIs had greater ECL than those with manual corneal incisions, suggesting that FL CCIs may negate some of the benefit of reduced phacoemulsification time on ECL. 77 More recently, in two randomised prospective studies by Dzhaber et al 78 in 134 eyes and Roberts et al 49 in 400 eyes showed no post-operative differences between FLACS and CPS at 3 and 1 month, respectively.…”
Section: Fl-assisted Nuclear Fragmentationmentioning
confidence: 94%
“…Several studies have investigated the possibility of reduced ECL after FLACS compared with CPS. 7578 One intra-individual study showed no difference between FLACS and CPS in ECL at 3 months. 76 While another study found that while there was no difference in ECL between eyes undergoing FLACs or CPS at 6 months, FLACS eyes with FL CCIs had greater ECL than those with manual corneal incisions, suggesting that FL CCIs may negate some of the benefit of reduced phacoemulsification time on ECL.…”
Section: Fl-assisted Nuclear Fragmentationmentioning
confidence: 99%
“…Wang et al reported no statistical significant differences in CCT between MICS and SICS. [46,48] Other authors in their studies also were no noted any differences in CCT between studied groups. [34,40,45,50] On the other hand, the irrigation solution volume used during the entire procedure should be taken into account.…”
Section: Discussionmentioning
confidence: 78%
“…[[11-13,39-44] In contrary to our study Bascaran et al did not found significant differences between the two groups in endothelial cell density loss and CCT either. [45,46] In turn, in the group B and in the group C there were no statistically significant differences in the loss of endothelial cells between studied groups. Similarly to our study Mencucci et al and Wang et al were no found significant differences in corneal endothelial cell loss or endothelial morphology between MICS and standard incision techniques.…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have investigated the effect of FS laser-assisted cataract surgery on anterior chamber in ammation and corneal endothelium [16][17][18]. Furthermore, the effects of LASIK performed with MMKs, excimer laser with super cial ablation as photorefractive keratectomy (PRK), and even radial keratotomy and intrastromal rings on in ammation in the anterior chamber have been investigated [12,19,20].…”
Section: Introductionmentioning
confidence: 99%